Culture, Growth and Economic Policy - Petrakis, Panagiotis E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
It is a wide-spread belief that the cultural background inhered in a society affects the requirements of economic development. This relationship requires theoretical and empirical justification. The present book provides this together with an analysis of the development of cultural background itself. Cultural background is embodied in political institutions, in transactions, knowledge, incentives, in social capital, even in the tangibles of the economy. Thus, economic development is shaped and the rate of growth is affected. Conversely, economic development affects cultural background. When this interaction takes place at a non-developmental cultural background level, which is associated with low growth rates, then a growth trap is formed. Within such a growth trap, economic policy (public and monetary) is relatively deactivated, and the conditions influencing the change in cultural background and its timing are of primary importance.
Introduction -- The Foundations: Human Needs and Cultural Background -- Culture in Economic Thinking -- Cultural Background and Economic System -- The Effect of Cultural Background on Incentives, Growth and Distribution and Vice Versa -- Cultural Background and Rationality -- The Cultural Dimensions and the Cultural Background Change: Cultural Surveys -- Collectivism as an Air or Obstacle to Economic Growth -- Power Distance, Uncertainty, Time and Growth -- The Cultural Background Change -- Cultural Background, Growth and Policy: Economic Growth and Cultural Background -- Cultural Background, Transaction Costs and Economic Institutions -- The Effects of Culture, Transactions and Institutions on Opportunity Entrepreneurship -- The Effects of Cultural Background and Knowledge Creation on Self-Employment and Entry Density Rates -- Cultural Background Growth and Economic Policy.
Keywords: Economics; Development Economics; Endogenous growth (Economics).; Economics/Management Science; Economic Growth; Cultural Studies; Development Economics; Economic Theory; Political Economy